Environmentally Friendly Cassava Starch-Based Hydrogel as Absorbent with Slow Release of Fertilizer - Bui, Phuong Dong; Nguyen, Thanh Huy; Nguyen, Bui Anh Duy; Chau, Phuoc Thiep; Nguyen, Chi Thanh (Journal of Technical Education Science, 2025)
The environmentally friendly cassava starch-based hydrogel with controlled slow release of fertilizer replacing for fossil-based hydrogels was prepared successfully by oxidation of cassava starch using a simple reaction. The physiochemical properties of obtained hydrogel were evaluated by some reliable analytical techniques such as: X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), scanning electron microscope (SEM), swelling ability in distilled water and various salt solutions. The XRD results showed the specific diffraction peaks corresponding to V-type crystals of starch. The results from FTIR analysis indicated the new peaks attributed to the stretching vibrations of bonding of aldehyde and carboxyl groups in the chemical structure of oxidized cassava starch. The surface morphological analysis of native cassava starch presented the smooth spherical shape. The dramatical change in morphology of hydrogel compared to that of the native cassava starch was found with the formation of a network of starch particles sticking together. The results from swelling degree of hydrogel showed that the fast water absorption at the early stage and reached the equilibrium stage in the long time of absorption. The swelling of hydrogel in salt solutions was found to be reduced with the increase of ion radius. Absorption and desorption results indicated that the obtained hydrogel had ability to absorb and release slowly some types of fertilizers such as: Urea, KNO3, (NH4)2SO4. This indicates that the obtained cassava starch-based hydrogel can be used as an environmentally friendly absorbent with slow release of fertilizers, having high potential for smart agricultural application.